In vivo determination of organellar pH using a universal wavelength-based confocal microscopy approach - Pineda Rodó, Albert; Váchová, Libuše; Palková, Zdena (PloS one, 2012)
Many essential cellular processes are affected by transmembrane H(+) gradients and intracellular pH (pHi). The research of such metabolic events calls for a non-invasive method to monitor pHi within individual subcellular compartments. We present a novel confocal microscopy approach for the determination of organellar pHi in living cells expressing pH-dependent ratiometric fluorescent proteins. Unlike conventional intensity-based fluorometry, our method relies on emission wavelength scans at single-organelle resolution to produce wavelength-based pH estimates both accurate and robust to low-signal artifacts. Analyses of Ato1p-pHluorin and Ato1p-mCherry yeast cells revealed previously unreported wavelength shifts in pHluorin emission which, together with ratiometric mCherry, allowed for high-precision quantification of actual physiological pH values and evidenced dynamic pHi changes throughout the different stages of yeast colony development. Additionally, comparative pH quantification of Ato1p-pHluorin and Met17p-pHluorin cells implied the existence of a significant pHi gradient between peripheral and internal cytoplasm of cells from colonies occurring in the ammonia-producing alkali developmental phase. Results represent a step forward in the study of pHi regulation and subcellular metabolic functions beyond the scope of this study.
Keywords: organely; Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; Green Fluorescent Proteins; membránové transportní proteiny; koncentrace vodíkových iontů; Luminescent Proteins; luminescentní proteiny; Membrane Transport Proteins; Microscopy, Confocal; Saccharomyces cerevisiae Proteins; Red Fluorescent Protein; zelené fluorescenční proteiny; Hydrogen-Ion Concentration; Organelles; červený fluorescenční protein; konfokální mikroskopie